A case of sudden death after ultrasound-guided percutaneous alcohol injection of a paraganglioma mis-diagnosed as a peri-renal cyst. (August 2015) - Andrello, L.; Visonà, S.D.; Osculati, A.
Highlights: Paragangliomas can cause sudden death. Paragangliomas are often clinically silent. The misdiagnosis could lead to wrong, life-threatening therapeutic procedures. They can be seen for the first time at autopsy. Abstract: Paragangliomas are cromaffin tumors arising from the neural crest cells of parasympathetic or sympathetic ganglia. They are known to be rare causes of sudden death. Here we present the autopsy findings, as well as microscopical and immunohistochemistry study, of a 48-years-old woman who died suddenly after a percutaneous alcohol injection of a peri-renal cyst previously diagnosed as a common complex cyst. She manifested a multiorgan failure, with acute heart failure, systemic and pulmonary vasoconstriction with hypoxia, metabolic acidosis (pH 6.974). It was therefore enacted resuscitation that was ineffective. The autopsy pointed out, close to the upper right renal pole, a cyst characterized by very friable walls and septa, with a thickness of approximately 0.5 cm and containing about 75 cm 3 of hemoserous fluid. Microscopically, through immunohistochemical examinations, the cyst showed the presence of chromaffin cells, containing enzymes involved in the synthesis of catecholamines, in particular noradrenalin. So, the cause of the death was ascertained in an multi-organ failure caused by a massive release of catecholamines (noradrenaline) from the cyst, identified post-mortem (on the basis of histologic and immunohistochemical examinations) in a noradrenalin-secreting paraganglioma, that remained silent until the cyst ablation.